2020
DOI: 10.3389/fpls.2020.00655
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Vacuolar H+ -Pyrophosphatase and Cytosolic Pyrophosphatases Causes Fatal Developmental Defects in Arabidopsis thaliana

Abstract: The cytosolic level of inorganic pyrophosphate (PPi) is finely regulated, with PPi hydrolyzed primarily by the vacuolar H +-pyrophosphatase (H +-PPase, VHP1/FUGU5/AVP1) and secondarily by five cytosolic soluble pyrophosphatases (sPPases; PPa1-PPa5) in Arabidopsis thaliana. Loss-of-function mutants of H +-PPase (fugu5s) have been reported to show atrophic phenotypes in their rosette leaves when nitrate is the sole nitrogen source in the culture medium. For this phenotype, two questions remain unanswered: why do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Mutants and all transgenic plants were in the Columbia-0 (Col-0) background, and Arabidopsis thaliana Col-0 was used as the wild type (WT). fugu5-1 and fugu5-3 were isolated and characterized as the loss-of-function mutant of the vacuolar type-I H + -PPase (Horiguchi et al, 2006b;Ferjani et al, 2007;Ferjani et al, 2011;Fukuda et al, 2016;Segami et al, 2018;Fukuda et al, 2020;Gunji et al, 2020;Gunji et al, 2022). pecp2-1 and pecp2-3 (previously described as ppspase1-1 or ps2-1, and ppspase1-3, respectively), pecp1-1, the fugu5-1 pecp2-1 pecp1-1 triple homozygous mutant (Hanchi et al, 2018), and the vhp2;1 and vhp2;2-2 (Segami et al, 2010) loss-of-function mutants were previously reported.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mutants and all transgenic plants were in the Columbia-0 (Col-0) background, and Arabidopsis thaliana Col-0 was used as the wild type (WT). fugu5-1 and fugu5-3 were isolated and characterized as the loss-of-function mutant of the vacuolar type-I H + -PPase (Horiguchi et al, 2006b;Ferjani et al, 2007;Ferjani et al, 2011;Fukuda et al, 2016;Segami et al, 2018;Fukuda et al, 2020;Gunji et al, 2020;Gunji et al, 2022). pecp2-1 and pecp2-3 (previously described as ppspase1-1 or ps2-1, and ppspase1-3, respectively), pecp1-1, the fugu5-1 pecp2-1 pecp1-1 triple homozygous mutant (Hanchi et al, 2018), and the vhp2;1 and vhp2;2-2 (Segami et al, 2010) loss-of-function mutants were previously reported.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Increased PPi levels in fugu5 are associated with inhibited hypocotyl elongation in etiolated seedlings (Ferjani et al, 2011). Seedlings grown in the light also display an altered cotyledon shape, as well as modifications of their palisade tissues, adaxial-side pavement cell complexity and stomatal distribution (Ferjani et al, 2007;Ferjani et al, 2011;Asaoka et al, 2019;Fukuda et al, 2020;Gunji et al, 2020;Gunji et al, 2022). These characteristics can be rescued by expressing IPP1, a soluble yeast pyrophosphatase (Ferjani et al, 2011;Segami et al, 2018;Gunji et al, 2020;Gunji et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations